Sweet fruits - good for everyone?: record of the international expert meeting of the German Commission for Justice and Peace on 16 January 2014 in Berlin ; rural development through self-organisations, value chains and social standards - Richard, Luise; Hagemann, Hildegard (Schriftenreihe Gerechtigkeit und Frieden, 2014)
Literaturverz. S. [81] - 84